Measurements with purpose: applied economics in action - Andrade López, Robert Santiago; Rivera Vasco, Tatiana Carolina; Ibarra Medina, Lina Marcela; Generale, Giovanni; Álvarez Caro, Diego Alejandro; González Rojas, Maria Carolina (2022)
The presentation shows multiple examples of research activities carried by the Foresight and Applied Economics unit, remarking the importance to generate measurements with purpose. The examples aim to inform our partner the International Center for Biosaline Agriculture on the relevance to take data-driven decisions that support research and enhance scaling-up of agricultural innovations.